Mechanisms for Improving the Capital Position of Commercial Banks - Ernazarov Narmet Saparbayevich (Peerian Journals Publishing, 2023)
The transition to a two-tier banking system, the establishment of economically independent commercial banks, the transition to the principle of self-financing of banks, the problem of achieving compatibility of liabilities and assets have become urgent issues in banking activity. The development of market relations led to the diversification of bank resources. Given the current economic conditions, it is advisable for banks to further develop the issue of attracting deposits in the formation of bank resources, because they will facilitate the payment system and facilitate the use of monetary policy tools by improving the accounting practices of the Central Bank. In these respects, the topic is relevant.
Keywords: private capital; bank; strategy